The impact of a cognitive information processing intervention on dysfunctional career thoughts and vocational identity in high school students - Strohm, David A. (Kansas State University, 2008)
This study examined the impact of two career interventions on the dysfunctional career thoughts (DCTs) and vocational identity (VI) of 55 high school seniors. Research has shown an inverse relationship between levels of DCTs and VI. One intervention was based on the Cognitive Information Processing approach (Peterson, Sampson, & Reardon, 1991; Peterson, Sampson, Lenz, & Reardon, 2002; Peterson, Sampson, Reardon, & Lenz, 1996; Sampson, Reardon, Peterson, & Lenz, 2004) and incorporated Improving Your Career Thoughts: A Workbook for the Career Thoughts Inventory (CTI workbook; Sampson, Peterson, Lenz, Reardon, & Saunders, 1996c) and the Self-Directed Search (SDS; Holland, 1994). The second intervention employed only the SDS. A control group used neither activity. Levels of DCTs and VI were assessed pre-intervention and post-intervention using the Career Thoughts Inventory (Sampson, Peterson, Lenz, Reardon, & Saunders, 1996a) and the Vocational Identity scale of My Vocational Situation (Holland, Daiger, & Power, 1980a). Earlier studies indicated improvements in levels of dysfunctional career thinking after CIP-based interventions (e.g., Kilk, 1998; Morano, 2005; Reed, 2006), but no previous studies employed the complete CTI workbook. Additional studies (e.g., Loughead & Black, 1990; Mau,1999; Wiggins, 1987) indicated that levels of vocational identity could be increased by using the SDS as an intervention. The combined use of the CTI workbook and SDS produced significant improvements in all five measures of DCTs and VI. It was also shown that use of the SDS as a stand-alone intervention did improve levels of VI, but not to the extent of the improvements shown by combined use of the SDS and CTI workbook. Use of the SDS as a stand-alone intervention did not produce improvements in levels of DCTs. The control group, which employed neither the CTI workbook nor the SDS, unexpectedly showed significant improvements in scores for two CTI scales which may have been due to the influence of confounding variables.
Keywords: Career Thoughts Inventory; Dysfunctional career thoughts; Vocational identity; Cognitive Information Processing; Self-Directed Search; Education, Guidance and Counseling (0519)